Comparative Analysis of Hotel Cost Efficiency Across Indonesian Regions - Abdul Ghofur; Hendri Kurniawan; Ahmad Muthohar; Dyah Palupiningtyas (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
The Indonesian hospitality industry is currently facing a post-pandemic "profitability paradox," a phenomenon where increased occupancy rates do not guarantee a proportional increase in net profit margins due to persistent operational cost inflation. This study aims to evaluate operational cost efficiency strategies and their impact on profitability across three star-rated hotels with contrasting locational and market characteristics: @Hom Hotel Kudus (Central Java), Grand Verona Samarinda (East Kalimantan), and FUGO Hotel Banjarmasin (South Kalimantan). This research adopts a descriptive qualitative approach with a comparative multiple-case study design. Data were collected through in-depth interviews with top management, participant observation, and financial document analysis. The results reveal that geographical characteristics and market segments are the primary determinants in selecting efficiency strategies. (1) Hom Hotel Kudus, located in a secondary industrial area, implements Lean Operations strategies through workforce multi-skilling to address market price sensitivity. (2) Grand Verona Samarinda, in the East Kalimantan business hub, focuses on Supply Chain Engineering by localizing raw materials to mitigate high logistical costs. (3) FUGO Hotel Banjarmasin, in the lifestyle segment, adopts Technology-Driven Efficiency to suppress utility costs without degrading the guest experience. The study concludes that sustainable profitability is achieved not through aggressive cost-cutting, but through strategic cost management adaptive to local contexts. These findings provide a new managerial framework for the hospitality industry to shift from a revenue-centric orientation to value optimization.